Low Inrıdıum-Doped TiO2 Nanostructure for Promısıng Photocatalyst ın Hexane Treatment - Ho, Van Thi Thanh; Nguyen, Ngan Thi Thanh; Chau, Dung Hung; Nguyen, Nhat Minh; Bui, Khang Quang; Nguyen, Long Tran Hoang; Le, Khang Huy; Truong, Son Nguyen (International Journal of Advanced Engineering Research and Science, 2021)
M-doped TiO2 (with M: noble metal) photocatalysts are being extensively applied for volatile organic compounds (VOCs) treatment because of their wide range of gaseous VOCs treating ability and their lower cost in comparison to other methods. However, the efficiency in removing volatile gaseous VOCs of M-doped TiO2 photocatalysts is relatively low due to the insufficient decrease of the band gap after doping (Eg < 3.0 eV), relatively low surface area (< 100 m2/g) for using sol-gel method in combination with thermal treating at high temperature (> ). In this work, we have solved current issues of TiO2 photocatalysts by synthesizing nano-scaled advanced-structured Ir-doped TiO2 materials in photocatalyst application for n-hexane decomposition, which has not been studied lately. The Ir-doped TiO2 photocatalyst is synthesized by one-stage hydrothermal method without using any surfactant or heating process after reactions. We found that the efficiency in n-hexane treatment of Ir-doped TiO2 photocatalyst with different ratios is relatively higher than other previous studies. It can be explained by the synthesis process of Ir-doped TiO2 material optimizing nano-scaled particles (10-15mm), large surface area (170 m2/g) and good crystallinity with the combination of anatase phase and rutile phase. Specially, Ir doping reduces the band gap of Ir-doped TiO2 material from 2.5 to 2.7 eV, compared to 3.2eV of undoped -TiO2 material’s band gap, depending on the doping ratio in which the function of doped Ir metal is affecting the activity in photoreaction of TiO2 by electrons or holes “traping” mechanism changing the electron/hole combination rate, hence enhancing the n-hexane treating efficiency.